A note on resource allocation scheduling with group technology and learning effects on a single machine. Issue 9 (2nd September 2017) - Lu, Yuan-Yuan; Wang, Ji-Bo; Ji, Ping; He, Hongyu
ABSTRACT: In this article, single-machine group scheduling with learning effects and convex resource allocation is studied. The goal is to find the optimal job schedule, the optimal group schedule, and resource allocations of jobs and groups. For the problem of minimizing the makespan subject to limited resource availability, it is proved that the problem can be solved in polynomial time under the condition that the setup times of groups are independent. For the general setup times of groups, a heuristic algorithm and a branch-and-bound algorithm are proposed, respectively. Computational experiments show that the performance of the heuristic algorithm is fairly accurate in obtaining near-optimal solutions.